Teachers' readiness to Use Mobile Gamification in Teaching and Learning in Primary Schools in South Kinta District - Anamalai, Tasaratha Rajan; Yatim, Maizatul Hayati Mohamad (Journal of Education for Sustainability and Diversity, 2022)
This study examined Teachers' readiness to use mobile gamification in teaching and learning (T&L) activities at primary schools in the South Kinta District. A quantitative approach with a questionnaire as a research instrument had been selected for this study. The sample consisted of 180 primary school teachers at South Kinta District. Study variables included in the study were; perceptions of teachers’ readiness; knowledge of teachers’ readiness, skills of teachers’ readiness; and challenges as well as issues. Results showed that all variables were at a moderate mean level as a whole; perceptions of teachers’ readiness (M = 2.87, SP = .455); knowledge of teachers’ readiness (M = 2.86, SP = .600); skills of teachers’ readiness (M = 2.61, SP = .554); and challenges and issues (M = 2.87, SP = .460). In conclusion, the results implied that the teachers' readiness to use mobile gamification in T&L at primary schools in the South Kinta District is at a moderate level and requires proactive efforts from school administrators and the Ministry of Education towards increasing teachers' interest.